Análisis de la calidad del empleo en los jóvenes de la parroquia Tenguel cantón Guayaquil provincia del Guayas, periodo 2014-2017 - Chasi Verdesoto, Joselyn Lissette (2018)
The research reviews the quality and access to employment for young people in the rural parish Tenguel belonging to the Guayaquil canton, province of Guayas, the objective was to determine the conditions of access to employment, characteristics of the same and conditions of the labor supply of the rural population of the segment of young people between 15 and 24 years old of the Tenguel parish of the Guayaquil canton, province of Guayas. For this purpose, the population was quantified in 2,098 young people between 15 and 24 years old, the calculated sample amounted to 282 individuals……